Numerical Visualization of Dielectric Barrier Discharge Plasma Actuator Surface Discharge - A., Ahmadi; Jane, Labadin; Pang, Piau (American Institute of Physics, 2011)
A single dielectric barrier discharge is a specific configuration for plasma actuators consisting of two electrodes, one coated by a dielectric material and the other is exposed to the air. The purpose of this paper is to study the characteristics of single dielectric barrier discharge (DBD) plasma actuator through numerical modeling. A mathematical model that represents the physical system is presented and the numerical simulations for specific geometry are discussed in this paper. With this model, we can study the physics of the plasma flow. The formulation of the governing equations are divided into two since the physical system can be distinctly separated; one is the electrostatic part and the other is on the fluid flow. The electrostatic part is formulated using the Maxwell’s equation which needs to be modified to incorporate the current frequency equation so that the system of equations becomes unsteady which is more realistic compared to a steady system of equations. The fluid flow part is formulated using the Navier-Stokes equations. The equations are re-represented using a vorticity term and stream function so that the flow characteristics can be clearly visualized. All equations are discretized using finite difference method. The discretized equations are then solved using the Gauss-Seidel iteration method. The numerical results show that the vorticity of the plasma is similar in pattern at each time interval. The highest magnitude of the vorticity occurs at the inner part near end of the upper electrode but this magnitude is different at each time. On varying the applied voltage, it is found that the peak vorticity also increases. Therefore, this shows that both the applied voltage and the geometry of the system influence the characteristics of the plasma flow.